Suicidal ideation during COVID-19: The contribution of unique and cumulative stressors. (April 2022) - Rudenstine, Sasha; Schulder, Talia; Bhatt, Krish J.; McNeal, Kat; Ettman, Catherine K.; Galea, Sandro
Highlights: The present study looked at correlates of suicidal ideation during COVID-19. Asian participants had higher odds of suicidal ideation. Participants with high cumulative stress, as well as those with high social and material stress, had higher odds of suicidal ideation. Abstract: The link between large-scale disasters and population-level risk of suicide remains unclear. The present study sought to investigate suicidal ideation (SI) in relation to COVID-19 related stress, including material and social stress, in a predominantly low-SES ethno-racially diverse sample in New York City during a peak in COVID-19 cases in April 2020. Using binary logistic regressions of data collected with self-report surveys, we found that individuals who identified as Asian, as well as those with high total, material, and social stress levels, and persons without access to primary care providers had significantly higher adjusted odds of SI. These results indicate the specific burden faced by Asian participants due to increases in targeted racism, the importance of cumulative stress and specific stressor type, as well as the role of healthcare access on SI during the pandemic. Such findings suggest the need for specific interventions that target individuals who may be at higher risk of suicide after large-scale traumatic events and during the ongoing pandemic.